Parusov E. V., Gubenko S. I., Sychkov A. B., Sahura L. V., Chuyko I. N. On behavior of non-metallic inclusions on different stages of deformation in the manufacture of high-strength wire - Парусов, Э.В.; Губенко, С.И.; Сычков, А.Б.; Сагура, Л.В.; Чуйко, И.Н. (Problems of Tribology, 2017)
The features of transformation of non-metallic inclusions are studied and the mechanism of their deformation at various technological stages of production of cold-deformed wire is analyzed. Material of the study: continuous casting of square section 125125 мм; hot-rolled steel with a diameter of 8,0 mm; cold-deformed wire with a diameter of 3,0 mm of high-carbon steel C86D. It is shown that non-metallic inclusions have a significant influence on the processes of the structure formation of steels of the pearlite class. In the process of steel deformation both in hot-rolling and cold-plastic deformation, the character-istic feature is the formation of vortex zones, which indicates an inhomogeneous distribution of stresses near the inclusions and their constant redistribution during the transition from one deformation focus to the other. Due to the different phase plasticities of heterophase inclusions, their destruction along interphase boundaries can be observed. When drawing at the boundaries of the inclusion section with the matrix, more stresses are concentrated than in hot rolling. This is due to the fact that with increasing total reduction of the metal, the plasticity of the matrix decreases and its flow along the interface with the inclusion is hampered. Key words: non-metallic inclusions, high-carbon steel, rolled steel, wire, deformation